Legal Protection for Tumor Surgeons on the Side Effects in Breast Cancer Chemotherapy Services - Yuyut Prayuti; Arman Lany; Zainal Abidin; Tofan Halim; Verasonti Dersiana; Rendy Rahmawan (PT ARRUS Intelektual Indonesia, 2024)
Legal protection for tumor surgeons in facing chemotherapy side effects in breast cancer patients is essential in contemporary medical practice. This study employed a narrative method and legal approach to explore the legal protection available to tumor surgeons in addressing risks and side effects during chemotherapy services. The narrative method was used to explore the role of the law in protecting tumor surgeons and providing a clear framework for addressing side effects in chemotherapy services. Literature analysis regarding medical practice standards, professional responsibilities, and relevant legal cases were used to formulate a comprehensive perspective of this legal protection. The research highlights the need for meticulous documentation of procedures, risks, and patient consent before undergoing chemotherapy. Additionally, legal protection also depends on adherence to applicable medical practice standards and effective communication between tumor surgeons and patients. In conclusion, the understanding of tumor surgeons is needed for the legal implications of their medical practices, including in the context of chemotherapy services. Thus, the use of narrative methods in this study provides valuable insights for tumor surgeons to protect themselves and provide safe and quality services to breast cancer patients.